Catalysis in electrochemistry from fundamental aspects to strategies for fuel cell development - Santos, Elizabeth; Schmickler, Wolfgang (Hoboken, N.J. : Wiley, 2011)
"Catalysis in Electrochemistry: From Fundamental Aspects to Strategies for Fuel Cell Development is a modern, comprehensive reference work on catalysis in electrochemistry, including principles, methods, strategies, and applications. It points out differences between catalysis at gas/surfaces and electrochemical interfaces, along with the future possibilities and impact of electrochemical science on energy problems. This book contributes both to fundamental science; experience in the design, preparation, and characterization of electrocatalytic materials; and the industrial application of electrocatalytic materials for electrochemical reactions. This is an essential resource for scientists globally in academia, industry, and government institutions."--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Electrocatalysis; Electronic books